Relationality - Lejano, Raul P.; Shan Kan, Wing (Cambridge University Press, 2024)
This Element sketches a conceptual framework for the study of relationality and illustrates some of the promise of relational analysis using an extended case study. This title is also available as Open Access on Cambridge Core.